Utilization of family medicinal plants as an effort to prevent stunting in Kalibaru Village, Cirebon Regency - Rima Yulia Senja; Muhamad Kusnendar; Popi Sri Wahyuni; Nenden Anindya; Nisa Dwi Nurindah; Tiara Salsabila; Rima Anggrie Difanti; Hurun’in Nur Auliya; Bagus Hermawan; Erik Ego Fajri; Latifah Latifah; Azzahra Maharani Kuswanto (Community Empowerment, 2023)
Kalibaru Village is one of the villages in the Tengah Tani District of Cirebon Regency, where 13 toddlers are affected by stunting conditions. The aim of this community service initiative is to promote the utilization of family medicinal plants (TOGA) as part of the effort to support government programs aimed at reducing stunting rates. The methods employed include socialization, TOGA planting, and the production of food products from family medicinal plants. The program's results revealed that 23.33% of the community had engaged in planting family medicinal plants, and the community's knowledge regarding TOGA, stunting and its prevention, and the use of TOGA in preventing stunting increased by 40.00%, 43.33%, and 66.67%, respectively. Furthermore, people's skills in processing medicinal plants into health food products increased by 56.67%.